Persistant sock-line hyper-hypopigmentation. - Karaca, Z. (European Journal of Pediatric Dermatology, 2020)
Sock-line hyperpigmentation has been described in Caucasian, Asian, African, and American infants. It is generally characterized by hyperpigmented palpable or nonpalpable horizontal patches on the extremities, consistent with bilateral or unilateral contact areas of socks and gloves (4). The etiology is not clearly understood, but it is thought to be associated with dermal inflammation or panniculitis caused by continuous compression and leading to post-inflammatory hyperpigmentation (5). A small portion of the reported lesions were biopsied and histopathology demonstrated lentiginous melanocytic hyperplasia and hyperpigmentation in the basal layer (1). It is important to distinguish clinically this disorder from child abuse, amniotic band syndrome and acquired raised bands of infancy. […]